Immediate effect of ankle joint and rectus abdominis kinesiology taping on static and dynamic balance in rhythmic gymnasts aged 10-12 years - Dudoniene, V.; Rimdeikiene, I.; Lapinskas, E. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Balance is a critical component of athletic performance, particularly in disciplines such as rhythmic gymnastics. This study aimed to examine the immediate effects of kinesiology taping on static and dynamic balance in rhythmic gymnasts aged 10-12 years.